Learning Curve of Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy – an Analysis of Critical Perioperative and Surgical Outcomes among 155 Peritoneal Surface Malignancy Patients Treated at a Tertiary Care Cancer Centre. Issue 7 (July 2022) - Saikia, J.; Deo, S.; Ray, M.; Mishra, A.; Bansal, B.; Bhoriwal, S.; Bhatnagar, S.; Mishra, S.; Bharti, S.J.; Kumar, V.; Kumar, M.
Abstract: Aims: Various factors can influence the learning curve of cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC). Initiating CRS and HIPEC programmes in low- and middle-income countries is challenging due to resource constraints and limited availability of expertise. We present our experience of CRS and HIPEC from a learning curve perspective among a cohort 155 peritoneal surface malignancy patients. Materials and methods: Patients undergoing CRS and HIPEC between May 2015 and February 2019 were included in the study. Patients were divided into two consecutive cohorts: the first 73 cases comprised the learning phase, group 1; the subsequent cohort of 82 patients were considered as the implementation phase, group 2. A comparative analysis of clinical and surgical outcome parameters was carried out between the two groups. Results: The clinical spectrum was comparable among group 1/group 2. Most were ovarian (56.8%), colorectal (13.5%) and appendiceal (11.0%) malignancies. Group 2 had a higher number of moderate to high peritoneal cancer index patients (34.1% versus 19.1%), total peritonectomies (48.8% versus 45.2%), multi-visceral resections (colonic 41.5% versus 27.4%, small bowel 25.6% versus 19.1%, diaphragmatic 8.5% versus 6.5% and hepatic resections 8.5% versus 2.7%) and completeness of cytoreduction 0/1 rates (97.6% versus 93.1%). A lower incidence of intraoperative urological injuries (2.6% versus 12.3%) was noticed in group 2 ( P = 0.007). Non-significant improvements seen in group 2 included surgery duration (6.0 ± 1.3 h versus 6.4 ± 1.7 h), intensive care unit stay (1.3 ± 1.1 days versus 1.8 ± 1.5 days), overall hospital stay (8.1 ± 0.9 days versus 8.8 ± 1.4 days) and reduction in Clavien-Dindo grade 3–4 complications (25.4% versus 36.9%). Conclusions: The results of the current study indicate that by implementing standard protocols and mentoring by an experienced team, a learning curve of CRS and HIPEC can be achieved in fewer than 75 cases. The baseline expertise of the treating team can also influence the learning curve. Highlights: Teams mentoring, HIPEC standardisation and broad specialty training helps to deal with complex cases over time. An improvement in key surgical outcome and quality indicators were observed after the initial learning phase. All these factors can help to save valuable resources and shorten the learning curve among LMICs and beginner centres.